Solve:x/3+4/3=2/3(4x-1)-(2x-x+1/3)
Answers
Answered by
19
Given: The expression x/3 + 4/3 = 2/3(4x - 1) - (2x - (x+1)/3)
To find: Solve for x?
Solution:
- Now consider: x/3 + 4/3 = 2/3(4x - 1) - (2x - (x+1)/3)
x + 4 / 3 = 2/3(4x - 1) - ((6x - x - 1) / 3)
x + 4 / 3 = { 2(4x - 1) - (5x - 1) } / 3
- Cancelling 3 from both sides, we get:
x + 4 = { 2(4x - 1) - (5x - 1) }
- Now solving further, we get:
x + 4 = 8x - 2 - 5x + 1
x + 4 = 3x - 1
x - 3x = -1 - 4
-2x = -5
x = 5/2
Answer:
So the value of x is 5/2.
Answered by
6
Answer:
heya
Step-by-step explanation:
answer is 15/6
Similar questions
Hindi,
7 months ago
Business Studies,
7 months ago
English,
7 months ago
Social Sciences,
1 year ago
Math,
1 year ago
Science,
1 year ago
Physics,
1 year ago